Ihsani social capital: a conceptual exploration to faith-inspired social capital - Malik, Maszlee (3KBioXML Publishers Pakistan, 2014)
The current Post-developmentalist discourse suggests amongst others, the effective role of social capital to development in its own unique way. Additionally, culture, religion, social networks and family institutions as part of the motivations that lead to ‘social capital’ are proposed by some researchers to have their significant role in the re- constructed concept of development, which transcend beyond growth and materialistic barometer. This study is an attempt to explore how Islam could contribute towards development of societies by establishing a unique model of social capital from its explicit ontological worldview through a directed descriptive epistemology. A deductive method is applied to its epistemological sources in explaining the emerging conceptual approach of ‘ihsani social capital’ that will lead towards development within the framework of ‘Social Capital’.